Advances in Artificial Intelligence in Manufacturing II Proceedings of the 2nd European Symposium on Artificial Intelligence in Manufacturing, October 16, 2024, Athens, Greece - Alexopoulos, Kosmas; Makris, Sotiris; Stavropoulos, Panagiotis; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book reports on recent developments of artificial intelligence applications in the manufacturing industry. Gathering contributions to the second European Symposium on Artificial Intelligence in Manufacturing, held on October 16, 2024, in Athens, Greece, it reports on machine learning, deep learning and generative AI models for process monitoring, optimization, and control, flexible and precise industrial robots, human-robot collaboration, data management and information technologies, digital twins, data augmentation and synthetic data. Giving a special emphasis to the integration of artificial intelligence in manufacturing systems, automation and processes, this book offers a timely and practice-oriented guide to a multidisciplinary audience of engineering researchers, system developers, AI scientists and industrial managers.
-- Part I AI in Process Level -- 1 Digital Twins of manufacturing processes under Industry 5.0 -- 2 Recurrent Convolutional Neural Network based defect detection in Submerged Arc Welding processes -- 3 On the use of Generative AI to support in-line process monitoring in Zero-Defect Manufacturing -- 4 Laser Metal Deposition (LMD) process monitoring: from 3D visualization of sensor data towards anomaly detection -- 5 An explainable active learning approach for enhanced defect detection in manufacturing, etc.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Control engineering; Robotics; Automation; Industrial engineering; Production engineering; User interfaces (Computer systems).; Human-computer interaction; Control, Robotics, Automation; Industrial and Production Engineering; User Interfaces and Human Computer Interaction